Search for the decays B(s)0→e+μ- and B(s)0→e+e- in CDF run II - Aaltonen, T; Adelman, J; Akimoto, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We report results from a search for the lepton flavor violating decays Bs0→e+μ- and B0→e+μ-, and the flavor-changing neutral-current decays Bs0→e+e- and B0→e+e-. The analysis uses data corresponding to 2fb-1 of integrated luminosity of pp̄ collisions at s=1.96TeV collected with the upgraded Collider Detector (CDF II) at the Fermilab Tevatron. The observed number of B0 and Bs0 candidates is consistent with background expectations. The resulting Bayesian upper limits on the branching ratios at 90% credibility level are B(Bs0→e+μ-)<2.0×10-7, B(B0→e+μ-)<6.4×10-8, B(Bs0→e+e-)<2.8×10-7, and B(B0→e+e-)<8.3×10-8. From the limits on B(B(s)0→e+μ-), the following lower bounds on the Pati-Salam leptoquark masses are also derived: MLQ(Bs0→e+μ-)>47.8TeV/c2, and MLQ(B0→e+μ-)>59.3TeV/c2, at 90% credibility level. © 2009 The American Physical Society.